Numerical investigation on effect of aortic root geometry on flow induced structural stresses developed in a bileaflet mechanical heart valve - Abbas, S.S. (Institute of Physics Publishing, 2017)
Structural stresses developed in an artificial bileaflet mechanical heart valve (BMHV) due to pulsed blood flow may cause valve failure due to yielding. In this paper, von-Mises stresses are computed and compared for BMHV placed in two types of aortic root geometries that are aortic root with axisymmetric sinuses and with axisymmetric bulb, at different physiological blood flow rates. With BMHV placed in an aortic root with axisymmetric sinuses, the von-Mises stresses developed in the valve were found to be up to 47 higher than BMHV placed in aortic root with axisymmetric bulb under similar physiological conditions. High velocity vectors and therefore high von-Mises stresses have been observed for BMHV placed in aortic root with axisymmetric sinuses, that can lead to valve failure. © 2017 Published under licence by IOP Publishing Ltd.